Sarcoidosis: molecular mechanisms and therapeutic strategies - Danfeng Xu; Xiaohua Tao; Yibin Fan; Yan Teng (Molecular Biomedicine)
Abstract Sarcoidosis, a multisystemic granulomatous disease with unknown etiology, is characterized by formation of noncaseating granulomas, which can affect all organs. Recent studies have made outstanding achievement in understanding the pathology, etiology, genetics, and immune dysregulation involved in granuloma formation of sarcoidosis. Antigen stimulation in genetically predisposed individuals enhances the phagocytic activity of antigen-presenting cells, including macrophages and dendritic cells. CD4 + T cells initiate dysregulated immune responses and secrete significant quantities of inflammatory cytokines, including interleukin (IL)-2 and interferon-gamma (IFN-γ), which play a crucial role in modulating the aggregation and fusion of macrophages to form granulomas. The current therapeutic strategies focus on blocking the formation and spread of granulomas to protect organ function and alleviate symptoms. The efficacy of traditional treatments, such as glucocorticoids and immunosuppressants, has been confirmed in the management of sarcoidosis. Promising therapeutic agents encompass inhibitors of cytokines, like those targeting tumor necrosis factor (TNF)-α, as well as inhibitors of signaling pathways, such as Janus kinase (JAK) inhibitors, which exhibit favorable prospects for application. Although there has been progress in the identification of biomarkers for the diagnosis, prognosis, activity and severity of sarcoidosis, specific and sensitive biomarkers have yet to be identified. This review outlines recent advancements in the molecular mechanisms and therapeutic strategies for the sarcoidosis.